A SOSIOLINGUISTIK DALAM PEMBELAJARAN BAHASA INDONESIA: SOSIOLINGUISTIK DALAM PEMBELAJARAN BAHASA INDONESIA - Aprida Hasnitah; Eko Kuntarto; Meri Haryani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
Linguistics is the study of language, both as an object and in its function and development. The existence of language structures can be seen throughout history and is a special phenomenon, isolated from other social elements. Regarding the structure of language and the limitations it imposes (lexical semantics, phonology, morphology, syntax and functional stylistics), language is a very specific and separate social phenomenon. Some language elements and categories, their characteristics and structural variants cannot be translated and are unique to the language. There are a number of methods and approaches that focus on sociolinguistic studies, including: a) competence-based language teaching, b) communicative language teaching, c) natural approach, d) cooperative language learning. In addition, there are several explanations of the basic theories of sociolinguistics that are applied in schools, namely: a) language as a communication tool, b) language skills are broad, c) students are part of society